Crop-Diversification for Conservation of Water Resource and Agricultural Growth: A Comparative Dynamic Analysis. (December 2013) - Sasmal, Joydeb
This article has addressed the problem of overexploitation of ground water for irrigation and built up a theoretical model to demonstrate how crop diversification in favour of water-saving crops can help conservation of water resource and agricultural growth. The comparative dynamic analysis on the optimal path of ground water stock has been done using variational differential equation . The qualitative results in Phase-Diagram show that if R&D expenditure is increased by the government or input subsidy and price support is increased for less water-intensive crops, water conservation will increase in a dynamic perspective. JEL Classification: Q32 Q38, Q25, O13